Encapsulação de subproduto industrial de acerola em matriz composta de goma arábica e maltodextrina para aplicação em alimentos: desenvolvimento, caracterização e estabilidade - Carneiro, Alessandra Pinheiro de Góes (2017)
The agribusiness is one of the most expressive sectors of the Brazilian economy and it generates a large amount of waste that is currently being exploited as an economic benefit to producers and a beneficial effect on the environment. Nanotechnology in food products becomes an alternative to make use of different substances, such as bioactive compounds, increasing the stability and desirable characteristics of the same, such as color, nutritional composition and antioxidant compounds. It presents itself as an application tool for quality, food safety and in order to meet the demands of consumers for healthy products and enriched with natural products that can be used from waste processing fruit. This research proposed to encapsulate an industrial byproduct of acerola on arabic gum matrix and maltodextrin in order to develop particles that could be used as carriers of bioactive compounds. Initially the characterization of the pulp and by - product of the acerola was performed through pH, color, soluble solids, titratable total acidity, total sugars and reducers. The samples were submitted to the determination of vitamin C, phenolic compounds, carotenoids, anthocyanins, yellow flavonoids and total antioxidant activity. The extract that presented the best results was chosen to be encapsulated using gum arabic matrix and maltodextrin. Seven different formulations of nanoparticles were elaborated that were characterized, physically, physicochemically and chemically. The particle that presented the best results was selected to be added in acerola nectar, submitted to bioaccessibility analysis. Both the pulp and the by-product of acerola presented relevant results for polyphenols (1214.54 mgGAE / 100g and 5287.11 mgGAE / 100g, respectively) and vitamin C (1113.10 mg a.c./100g and 2726 mg a.c. / 100g, respectively). The nanoparticles presented as good sources of total polyphenols (954.26 to 2349.43 mg ac. /100 g), vitamin C (1146.75 to 4468.99 mg GAE / 100 g) and antioxidant activity (34.38 to 150.12 μM TROLOX / g), in addition to presenting bimodal particle size distribution, distribution heterogeneity and zeta potential representing stability in suspension. The nanoparticles presented as good sources of total polyphenols (954.26 to 2349.43 mg ac. /100 g), vitamin C (1146.75 to 4468.99 mg GAE / 100 g) and antioxidant activity (34.38 to 150.12 μM TROLOX / g), in addition to presenting bimodal particle size distribution, distribution heterogeneity and zeta potential representing stability in suspension. A (1GA: 1MA: 1EXT) and E (1GA: 1MA: 2EXT) nanoparticles were selected for evaluation of antimicrobial activity being efficient for inhibition of E. coli and L. monocytogenes and bactericidal for E. coli. The nanoparticles A and E were stable over a period of 6 months regarding the content of total polyphenols (3595.00 and 4920.19 mg GAE / 100g, respectively) and antioxidant activity (60.24 and 59.17 μM TROLOX / g, respectively). For vitamin C, the nanoparticle A remained stable during storage (1976.18 mg ac. /100 g), while the nanoparticle E showed a decrease over time (2446.11 to 1663.16 mg ac. / 100g). The gastrointestinal bioaccessibility of acerola nectar containing nanoparticles presented promising results for absorption of total polyphenols 9.59% for A and 8.62% for E and antioxidant activity 77.99% for A and 78.91% for E. It was concluded That the by-product of the processing of the acerola pulp presents characteristics to be used in processing for extraction of bioactive compounds to be encapsulated. The nanoparticles presented as sources of bioactive compounds and with sufficient stability to be added in food products.